Systematic review of human post‐mortem immunohistochemical studies and bioinformatics analyses unveil the complexity of astrocyte reaction in Alzheimer's disease. (17th August 2021) - Viejo, Lucía; Noori, Ayush; Merrill, Emily; Das, Sudeshna; Hyman, Bradley T.; Serrano‐Pozo, Alberto
Abstract: Aims: Reactive astrocytes in Alzheimer's disease (AD) have traditionally been demonstrated by increased glial fibrillary acidic protein (GFAP) immunoreactivity; however, astrocyte reaction is a complex and heterogeneous phenomenon involving multiple astrocyte functions beyond cytoskeletal remodelling. To better understand astrocyte reaction in AD, we conducted a systematic review of astrocyte immunohistochemical studies in post‐mortem AD brains followed by bioinformatics analyses on the extracted reactive astrocyte markers. Methods: NCBI PubMed, APA PsycInfo and WoS‐SCIE databases were interrogated for original English research articles with the search terms 'Alzheimer's disease' AND 'astrocytes.' Bioinformatics analyses included protein–protein interaction network analysis, pathway enrichment, and transcription factor enrichment, as well as comparison with public human ‐omics datasets. Results: A total of 306 articles meeting eligibility criteria rendered 196 proteins, most of which were reported to be upregulated in AD vs control brains. Besides cytoskeletal remodelling (e.g., GFAP), bioinformatics analyses revealed a wide range of functional alterations including neuroinflammation (e.g., IL6, MAPK1/3/8 and TNF), oxidative stress and antioxidant defence (e.g., MT1A/2A, NFE2L2, NOS1/2/3, PRDX6 and SOD1/2), lipid metabolism (e.g., APOE, CLU and LRP1), proteostasis (e.g., cathepsins, CRYAB and HSPB1/2/6/8), extracellular matrix organisation (e.g., CD44, MMP1/3 and SERPINA3), and neurotransmission (e.g., CHRNA7, GABA, GLUL, GRM5, MAOB and SLC1A2), among others. CTCF and ESR1 emerged as potential transcription factors driving these changes. Comparison with published ‐omics datasets validated our results, demonstrating a significant overlap with reported transcriptomic and proteomic changes in AD brains and/or CSF. Conclusions: Our systematic review of the neuropathological literature reveals the complexity of AD reactive astrogliosis. We have shared these findings as an online resource available at www.astrocyteatlas.org . Abstract : We aimed to define the functional changes characteristic of reactive astrocytes in Alzheimer's disease (AD) via a systematic review of immunohistochemical studies in post‐mortem AD brains followed by bioinformatics analyses (e.g., protein–protein interaction network, pathway and transcription factor enrichment); 306 eligible articles rendered 196 proteins, which underscore a complex phenotypic change involving inflammation, oxidative stress, lipid metabolism, proteostasis, extracellular matrix remodelling, neuromodulation and blood–brain barrier integrity, among other alterations. These markers were catalogued in a new online resource: www.astrocyteatlas.org .